Maternal physical activity-induced adaptive transcriptional response in brain and placenta of mothers and rat offspring. (17th June 2019) - Fragoso, Jéssica; Carvalho Jurema Santos, Gabriela; Thomaz da Silva, Helyson; Oliveira Nogueira, Viviane; Loizon, Emmanuelle; Vidal, Hubert; Costa-Silva, João Henrique; da Silva Aragão, Raquel; Pirola, Luciano; Leandro, Carol Gois
Abstract: Maternal physical activity induces brain functional changes and neuroplasticity, leading to an improvement of cognitive functions, such as learning and memory in the offspring. This study investigated the effects of voluntary maternal physical activity on the gene expression of the neurotrophic factors (NTFs): BDNF, NTF4, NTRK2, IGF-1 and IGF-1r in the different areas of mother's brain, placenta and foetus brain of rats. Female Wistar rats (n = 15) were individually housed in voluntary physical activity cages, containing a running wheel, for 4 weeks (period of adaptation) before gestation. Rats were classified as inactive (I, n = 6); active (A, n = 4) and very active (VA, n = 5) according to daily distance spontaneously travelled. During gestation, the dams continued to have access to the running wheel. At the 20 th day of gestation, gene expression of NTFs was analysed in different areas of mother's brain (cerebellum, hypothalamus, hippocampus and cortex), placenta and the offspring's brain. NTFs gene expression was evaluated using quantitative PCR. Very active mothers showed upregulation of IGF-1 mRNA in the cerebellum (36.8%) and NTF4 mRNA expression in the placenta (24.3%). In the cortex, there was a tendency of up-regulation of NTRK2 mRNA (p = 0.06) in the A and VA groups when compared to I group. There were no noticeable changes in the gene expression of NTFs in the offspring's brain. Our findings suggest the existence of a developmental plasticity induced by maternal physical activity in specific areas of the brain and placenta representing the first investment for offspring during development.